Cumulative HIV Viremia Copy-Years and Hypertension in People Living with HIV - Xu, Yunan; Chen, Xinguang; Wijayabahu, Akemi; Zhou, Zhi; Yu, Bin; Spencer, Emma C.; Cook, Robert L. (Current HIV Research, 2020)
Background: Evidence regarding the association between HIV viral load (VL) and hypertension is inconsistent. In this study, we investigated the relationship using viremia copy-years (VCY), a cumulative measure of HIV plasma viral burden. Methods: Data were analyzed for 686 PLWH in the Florida Cohort Study, who had at least five years of VL data before the baseline. VL data were extracted from Enhanced HIV/AIDS Reporting System (eHARS) and used to define peak VL (pVL), recent VL (rVL), and undetectable VL (uVL: rVL<50copies/mL). A five-year VCY (log10 copy x years/mL) before the baseline investigation, was calculated and divided into 5 groups (≤2.7, 2.8-3.7, 3.8-4.7, 4.8-5.7 and >5.7) for analysis. Hypertension was determined based on hypertension diagnosis from medical records. Multivariable logistic regression was used for association analysis. Results: Of the total sample, 277 (40.4%) participants were hypertensive. Compared to the participants with lowest VCY (≤2.7 log10 copy x years/mL), the odds ratios (OR) and 95% confidence interval [95% CI] for hypertension of the remaining four groups, in order, were 1.91 [1.11, 3.29], 1.91 [1.03, 3.53], 2.27 [1.29, 3.99], and 1.25 [0.65, 2.42], respectively, controlling for confounders. The association was independent of pVL, rVL, and uVL, each of which was not significantly associated with hypertension. Conclusion: Persistent HIV infection is a risk factor for hypertension among PLWH. Information provided by VCY is more effective than single time-point VL measures in investigating HIV infection- hypertension relationship. The findings of this study support the significance of continuous viral suppression in hypertension prevention among PLWH.
Keywords: viral load